Intermediasi Minat Beli Terhadap Keputusan Pembelian Melalui Digital Marketing Dan Citra Merek - Bintang Muhammad Irsyad; Rivera Pantro Sukma (LPPM and Travel Operation Department Universitas Asa Indonesia, 2023)
The purpose of this study is to determine the influence of digital marketing and brand image on purchasing decisions through buying intentions at Jozo Coffee Condet. Data collection by distributing questionnaires to consumers. The sampling technique uses accidental sampling method as many as 200 respondents. Data processing conducted by this study uses SmartPLS application version 3.2.9. The results of this study, there is a significant direct influence of digital marketing on buying intentions, digital marketing has a positive and significant effect on purchasing decisions, brand image has a positive and significant effect on buying intentions and brand image has a significant positive effect on purchasing decisions and for indirect influences, digital marketing through buying intentions has a significant effect on purchasing decisions, Also, brand image through buying intentions has a significant influence on purchasing decisions.